Acupuncture for cancer pain: protocol for a pilot pragmatic randomised controlled trial. Issue 7 (9th July 2019) - He, Yihan; May, Brian H; Zhang, Anthony Lin; Guo, Xinfeng; Liu, Yihong; Qu, Yanchun; Chang, Xuesong; Lu, Chuan-jian; Xue, Charlie Changli; Zhang, Haibo
Abstract : Introduction: Although acupuncture has been recommended for alleviating cancer pain by clinical guidelines, the level of the supporting evidence needs to be improved. A pragmatic randomised controlled trial (pRCT) in a hospital setting would provide real-world assessments of the overall clinical effects of acupuncture. This pilot trial aims to explore the feasibility and provide data for sample size calculations for a pRCT evaluating the effectiveness of acupuncture as an adjunctive therapy to routine medical care for cancer pain. Methods and analysis: Thirty patients with cancer admitted to the oncology department with moderate or severe pain will be recruited. Participants will be randomised at a ratio of 1:1 to the adjunctive acupuncture group or a control group which receives routine pain management without acupuncture. The standardised section of the acupuncture protocol will be developed based on the results of reviews of the literature, recommendations in clinical guidelines and interviews with clinical experts. The acupuncturist will be allowed to tailor the protocol according to the individual situation of each participant. Primary outcomes relevant to the feasibility of conducting a fully powered trial include: numbers and proportions of participants recruited, screened, consented and randomised; numbers and reasons for withdrawals and dropouts; numbers and types of adverse events; feasibility of implementing the trial procedures; evaluation of the comprehensiveness and ease-of-use of the case report form. Secondary outcomes are clinical measurements of the effectiveness of the treatment that are intended for use in the full-scale trial. Analysis of feasibility will be descriptive and pain intensity measures will be analysed using mixed-effects regression. Ethics and dissemination: Ethics approval was obtained from the Institutional Ethics Committee of Guangdong Provincial Hospital of Chinese Medicine (approval no: Z2017-184-01) and RMIT University Human Research Ethics Committee (reference no: 21361). Results will be disseminated in a peer-reviewed journal, and trial participants will be informed via email and/or phone calls. Trial registration number: ChiCTR1800017023